The Role of Defense Doctrine in Dealing with Nonmilitary Threats in the Economic Field - Tika Maidasari; Guntur Eko Saputro; Lukman Yudho Prakoso (JETISH: Journal of Education Technology Information Social Sciences and Health, 2023)
In 2020 Indonesia experienced a crisis with economic growth falling to -5.32%. Not only in Indonesia, this is also felt by the entire world the impact of the Covid-19 virus. Not over Covid-19, there has been a war between Russia and Ukraine which has also affected the global economy because the 2 countries are the main exporters of several strategic commodities on an international scale, causing disruptions to world supply chains. For this reason, there needs to be sustainable steps and actions so that the Indonesian economy continues to grow amid the threat of a global recession. The formulation of the problem to be examined is how the role of defense doctrine in dealing with non-military threats in the economic field. This article uses qualitative descriptive analysis research methods supported by several theories. The results show that defense doctrine plays an important role in increasing economic growth in Indonesia. Internal and external threats in the economy are expected to be overcome if defense doctrine is practiced sustainably.